Ian Frazer - King, Madonna 1965- (Univ. of Queensland Press, 2013)
When Professor Ian Frazer, was awarded the patent for the vaccine to cervical cancer, he knew it could help to save the lives of 275,000 women around the world each year.Respected across the globe, few people know the real story of the Scottish-born Australian of the Year who is behind one of the great medical discoveries of the century. Given exclusive access to Ian Frazer, biographer and award-winning journalist Madonna King peels back the many layers of his extraordinary life. She tells of the ongoing struggle for funding cancer research, the herculean international legal battle waged to win the patent, the devastating loss of his friend and co-researcher, Dr. Jian Zhou, and Ian Frazer's commitment to have the vaccine made available in the developing world
Includes index
Keywords: Frazer, I. H. / (Ian H.); Frazer, Ian Hector -- 1953-; Physicians / Australia / Biography; Cancer Vaccines / history / Australia; History, 20th Century / Australia; Immunologists / Australia / Biography; Medical scientists / Australia / Biography; Australien; Biografie